ASSESSING THE SUSTAINABILITY OF SPECIAL AUTONOMY FUNDS IN ACHIEVING DEVELOPMENT GOALS: THE CASE OF ACEH - Hendri Mauliansyah; Ammar Fuad (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2025)
This study assesses the sustainability of Special Autonomy Funds (SAF) in Aceh and their contribution to achieving sustainable development goals (SDGs) within a post-conflict context. Following the 2005 Helsinki Agreement, SAF was designed to support poverty reduction, improve education and health services, and accelerate infrastructure development. Employing a mixed-methods approach, the research integrates quantitative data from official statistics and surveys with qualitative insights from interviews, focus groups, and participatory observations involving government officials, NGOs, and community leaders. Findings show that while SAF significantly expanded access to education, healthcare, and basic infrastructure, governance challenges—including limited transparency, weak accountability, and uneven distribution—have constrained its effectiveness. Evidence of participatory budgeting demonstrates the potential of community engagement to enhance sustainability, yet institutionalization of inclusive mechanisms remains limited. Moreover, political dynamics and over-reliance on central transfers pose risks to the fund’s long-term stability. The study highlights three dimensions of sustainability: financial vulnerability due to fiscal dependence, social inclusivity challenges affecting marginalized groups, and environmental risks linked to poorly regulated infrastructure projects. To optimize SAF, policy recommendations include strengthening transparency through independent audits and digital monitoring, diversifying the local economy to reduce fiscal dependency, and embedding participatory governance to ensure equity. This research contributes to scholarly debates on fiscal decentralization in fragile regions while offering practical insights for policymakers and development practitioners seeking to align autonomy financing with sustainable development outcomes.